Social contacts and networks of refugees in the arrival context - Manifestations in a large city and in selected small and medium-sized towns - Adam, Francesca; Föbker, Stefanie; Imani, Daniela; Pfaffenbach, Carmella; Weiss, Günther; Wiegandt, Claus-Christian (ERDKUNDE, 2019)
The integration of refugees with prospects of remaining in the country has noticeably shifted into the focus of public attention and is presently being addressed in numerous research projects as well. Our contribution aims to address the significance, which the various contacts or networks, respectively, hold for the integration of the refugees. Issues of particular interest are how contacts to friends and families are maintained, what role these contacts play in the refugees’ daily lives, how new social contacts are established in the arrival context, and which factors may ease or hinder the creation of new contacts. Based on the assumption that integration processes of migrants and refugees are influenced to a large extent by the prevailing local context, we investigated whether there are differences between a metropolitan situation (city of Cologne) and a small or medium-sized setting (district of Heinsberg) in the social contacts and networks of the refugees. In both distinct local contexts, which are located in North Rhine-Westphalia (Germany), we conducted qualitative interviews with 41 refugees in total. All interviews were recorded, subsequently transcribed and analysed using a largely inductive category scheme. Due to the exceptional situation of the flight and the assignment of a place of residence by the state, similarly escaped relatives and friends from the past usually live in other parts of Germany or even in other countries, and therefore cannot serve as a localised network to cushion the individual’s arrival. Within the arrival context, contacts to other refugees who share the same or a similar background and language provide an important source of practical support and emotional backing. Bridging ties to members of the receiving society are most likely to be established through language courses and volunteer initiatives. Here, the openness and proactive attitude of the refugees prove to be an important factor. The metropolis offers abundant opportunities for new but fleeting social contacts. In the context of small and medium-sized towns, the greater manageability imbues the newly developing networks with greater stability.